Spatial patterns of pharmaceuticals and wastewater tracers in the Hudson River Estuary. (15th June 2018) - Cantwell, Mark G.; Katz, David R.; Sullivan, Julia C.; Shapley, Daniel; Lipscomb, John; Epstein, Jennifer; Juhl, Andrew R.; Knudson, Carol; O'Mullan, Gregory D.
Abstract: The widespread use of pharmaceuticals by human populations results in their sustained discharge to surface waters via wastewater treatment plants (WWTPs). In this study, 16 highly prescribed pharmaceuticals were quantified along a 250 km transect of the Hudson River Estuary and New York Harbor to describe their sources and spatial patterns. Sampling was conducted over two dry weather periods in May and July 2016, at 72 sites which included mid-channel and nearshore sites, as well as locations influenced by tributaries and WWTP outfalls. The detection frequency of the study pharmaceuticals was almost identical between the May and July sampling periods at 55% and 52%, respectively. Six pharmaceuticals were measurable at 92% or more of the sites during both sampling periods, illustrating their ubiquitous presence throughout the study area. Individual pharmaceutical concentrations were highly variable spatially, ranging from non-detect to 3810 ng/L during the study. Major factors controlling concentrations were proximity and magnitude of WWTP discharges, inputs from tributaries and tidal mixing. Two compounds, sucralose and caffeine, were evaluated as tracers to identify wastewater sources and assess pharmaceutical behavior. Sucralose was useful in identifying wastewater inputs to the river and concentrations showed excellent correlations with numerous pharmaceuticals in the study. Caffeine-sucralose ratios showed potential in identifying discharges of untreated wastewater occurring during a combined sewage overflow event. Many of the study pharmaceuticals were present throughout the Hudson River Estuary as a consequence of sustained wastewater discharge. Whereas some concentrations were above published effects levels, a more complete risk assessment is needed to understand the potential for ecological impacts due to pharmaceuticals in the Hudson River Estuary. Graphical abstract: Highlights: High resolution sampling shows the spatial distribution of pharmaceuticals. Tracers were successful in identifying and differentiating wastewater sources. Sucralose proved effective as a tracer for select pharmaceutical compounds. Wastewater discharges produce sustained, elevated levels of pharmaceuticals.